Usage patterns and social circles on Facebook among elderly people with diverse personality traits. Issue 4 (3rd April 2018) - Mo, Fan; Zhou, Jia; Kosinski, Michal; Stillwell, David
ABSTRACT: Elderly people are exposed to information technologies to keep them in touch with younger generations. Among various technologies, social network sites (SNSs) are seldom used by the majority of elderly people. To bridge the digital divide, it is necessary to dig deeply into the minority elderly users of SNSs. This study explores usage patterns of elderly Facebook users and further investigates how their diverse characteristics influence their usage and social circles. Three findings were derived. First, a sharp digital divide on SNSs does exist, and existing elderly Facebook users are mainly the dabblers. Second, personality profiling could predict elderly people's SNS usage behaviors. Elderly users with a high level of openness and extroversion have more friends, status updates, and group memberships, and those with a high level of conscientiousness have fewer likes and status updates. Elderly users are likely to seek insightful content on SNSs. Moreover, they may have a higher degree of emotional stability than young users when using SNSs. Third, elderly people tend to build small social circles on SNSs that "copy" the family relationship in the real world; whereas, they build large social circles with interests and hobbies that are difficult to share in the real world. Based on these results, detailed suggestions are presented for better targeting elderly people in ways that move them toward SNSs.